2009
DOI: 10.1136/bjsm.2008.057059
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative quadriceps strength is a significant predictor of knee function two years after anterior cruciate ligament reconstruction

Abstract: Preoperative quadriceps muscle strength deficits and meniscus injuries have significant negative consequences for the long-term functional outcome after ACL reconstruction. From our findings we suggest that ACL reconstruction should not be performed before quadriceps muscle strength deficits of the injured limb is less than 20% of the uninjured limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
282
3
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(304 citation statements)
references
References 61 publications
11
282
3
8
Order By: Relevance
“…Early symptoms predict postsurgical outcomes years after an ACL reconstruction. [24][25][26] Future longitudinal studies that assess whether baseline traumatic BML size can predict patient-reported outcomes years after surgery or that evaluate whether changes in traumatic BML size relate to changes in knee pain will help build on these findings. Second, it remains unclear if the associations presented here were confounded by inflammation or concurrent injuries (eg, meniscal injury or chondral lesions) that could have contributed to the development of both traumatic BML volumes and knee pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early symptoms predict postsurgical outcomes years after an ACL reconstruction. [24][25][26] Future longitudinal studies that assess whether baseline traumatic BML size can predict patient-reported outcomes years after surgery or that evaluate whether changes in traumatic BML size relate to changes in knee pain will help build on these findings. Second, it remains unclear if the associations presented here were confounded by inflammation or concurrent injuries (eg, meniscal injury or chondral lesions) that could have contributed to the development of both traumatic BML volumes and knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, preoperative knee and body pain are important predictors of postsurgical outcomes 1 or 2 years after an ACL reconstruction. 25,26 Thus, enhancing our understanding of the factors involved in posttraumatic pain may be important in improving long-term results for the ACL-injured population. To further clarify the relationships between traumatic BMLs and knee pain and symptoms, we explored the cross-sectional associations between posttraumatic BML volume and self-reported knee pain and symptoms within the first 4 weeks after an ACL injury.…”
mentioning
confidence: 99%
“…Extensive research demonstrates quadriceps deficits can be present at six months and even up to and exceeding one year. [1][2][3][4][5] Quadriceps strength has recently been shown to help predict reinjury rate. Grindem et al 20 found that individuals following ACL-R with a quadriceps strength deficit of greater than 10% are significantly more likely to reinjure their ipsilateral ACL.…”
Section: Discussionmentioning
confidence: 99%
“…Greater quadriceps strength pre-operatively has been correlated to increased quadriceps strength post-operatively. However, it is well documented that quadriceps strength deficits may remain for two years and beyond, following ACL-R. [1][2][3][4][5] Multiple authors have shown that those individuals with greater quadriceps strength pre-operatively have significantly greater quadriceps strength at RTS, and those with lower quadriceps strength pre-operatively have lower functional scores on single and triple hop tests (time and distance) at time of RTS and may take longer to RTS after ACL-R. 1, 2,6 Quadriceps strength is important as it relates to outcomes and performance at time of RTS. 2,7 Recently, researchers have found that decreased quadriceps strength, and larger asymmetries between limbs, lead to shorter distances on hop tests.…”
Section: Introductionmentioning
confidence: 99%
“…The concept was initially coined in the 1980s for professional athletes as a process to prevent unnecessary atrophy of muscle in order to prevent future injuries [101]. Preoperative quadriceps strength is an important predictor of the functional outcome of the knee joint after ACLR [102]. This paper focuses on exerciserelated prehabilitation in preoperative ACL patients.…”
Section: Exercise Before Aclr and The Role Of Prehabilitationmentioning
confidence: 99%